2008
DOI: 10.1682/jrrd.2007.04.0054
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nonmicroprocessor knee mechanism versus C-Leg on Prosthesis Evaluation Questionnaire, stumbles, falls, walking tests, stair descent, and knee preference

Abstract: Abstract-This study compared subjects' performance with a nonmicroprocessor knee mechanism (NMKM) versus a C-Leg on nine clinically repeatable evaluative measures. We recorded data on subjects' performance while they used an accommodated NMKM and, following a 90-day accommodation period, the C-Leg in a convenience sample of 19 transfemoral (TF) amputees (mean age 51 +/-19) from an outpatient prosthetic clinic. We found that use of the C-Leg improved function in all outcomes: (1) Prosthesis Evaluation Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
290
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(310 citation statements)
references
References 44 publications
17
290
2
1
Order By: Relevance
“…Seventh, none of our patients who had AKA used any of the new advanced prosthetic legs such as the C-leg (Otto Bock; Duderstadt, Germany). Kahle et al [17] reported that use of the C-leg improves performance and quality of life and can increase community ambulation level. This will add to the argument of defining the line between amputation and limb salvage.…”
Section: Discussionmentioning
confidence: 99%
“…Seventh, none of our patients who had AKA used any of the new advanced prosthetic legs such as the C-leg (Otto Bock; Duderstadt, Germany). Kahle et al [17] reported that use of the C-leg improves performance and quality of life and can increase community ambulation level. This will add to the argument of defining the line between amputation and limb salvage.…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing specific programs and sensor information, these prostheses may result in a more natural gait (Aaron et al, 2006;Sup et al, 2008;Herr and Wilkenfeld, 2003;Johansson et al, 2005;Kahle et al, 2008;Kapti and Yucenur, 2006;Laferrier and Gailey, 2010). The main differences in the design of these prostheses are in their damping systems because an adequate damping allows for fast transitions in stride velocity, which increases the autonomy of the amputee.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing a questionnaire, Kahle et al (2008) showed that subjects who use the hydraulic-based C-leg (commercialized by Otto Bock HealthCare Deutschland, Duderstadt, Germany) demonstrated an improved performance and higher quality of life compared to subjects who use nonmicroprocessor above-knee prostheses. Johansson et al (2005) reported a clinical comparison between two variable-damping above-knee prostheses (the hydraulic-based C-leg and magneorheological-based Ossur Rheo) and a passive mechanism (hydraulic-based Mauch SNSC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their complex interaction of various functional principles used for generating joint resistances are implemented by control algorithms and sensor technology that directly affect movement and safety outcomes for lower-limb amputees [2][3][4]. For the patient, the resultant functional quality [2,5,8,12,17,18,24,[30][31][32], and the reduction in falls some MPKs provide [3,7,11,16], is of central importance. The challenge for prosthetic practitioners and patients alike is how to select the appropriate MPK to meet the functional needs of the lower-limb amputee.…”
Section: Introductionmentioning
confidence: 99%